Febuxostat and Renal Outcomes in Stage 3-4 CKD Patients with Asymptomatic Hyperuricemia: A Prospective Observational Study (Journal of Rangpur Medical College, 2026)
Background: Chronic kidney disease (CKD) is commonly accompanied by asymptomatic hyperuricemia, which has been linked to faster renal deterioration. Objective: This study evaluated whether febuxostat provides renal benefit compared with standard care in adults with stage 3–4 CKD and elevated serum uric acid. Methods: This prospective observational study was conducted in the Department of Nephrology at the National Institute of Kidney Diseases & Urology (NIKDU), Dhaka, from February to July 2016, on 150 adults with chronic kidney disease (CKD) Stage 3-4 and asymptomatic hyperuricemia (serum uric acid ≥7 mg/dL), allocated in equal numbers by a closed-envelope technique to either a Febuxostat group (40 mg once daily after breakfast) or a conventional-therapy group receiving standard CKD care without Febuxostat (75 patients in each group). Participants were followed at baseline, 2 months, and 4 months with repeat clinical and biochemical assessments. The primary outcome was a ≥10% decline from baseline eGFR at 4 months. Secondary outcomes included between-group differences in CKD stage distribution, mean eGFR, and serum creatinine at 2 and 4 months, change in serum uric acid, and significant adverse events (myocardial infarction, stroke, heart failure, mortality). Results: Over four months, febuxostat was associated with better preservation of kidney function: eGFR remained higher, creatinine rose more slowly, and progression to CKD stage 5 was markedly lower. The primary endpoint, a ≥10% eGFR decline, occurred far less frequently with febuxostat, corresponding to a substantially reduced adjusted risk. Serum uric acid decreased to near-target levels, and cardiovascular events were infrequent and comparable between groups. Conclusion: These findings indicate the short-term renoprotective potential of febuxostat in selected CKD patients, underscoring the need for longer controlled trials.J Rang Med Col. March 2026; Vol.11, No.1: 3-8